(untitled) (Libellarium: journal for research in the field of information and related sciences, 2021)
This paper chronicles interventions to renovate and repurpose a community library in one of the poorest countries in the world; Malawi, where over 80% of the population lives below the poverty line (less than US1.25/day). This initial report is based on activities undertaken by a team of individuals with diverse expertise and cultural backgrounds, and a common vision for repurposing the Kwakupokela Community Library. To date, key achievements include: the Kwakupokela Educational Trust has been created and registered with the Malawi government as a non-governmental organization which now operates the library; a Memorandum of Understanding (MoU) has been signed with Mzuzu University; new books have been donated; and both new and old library books have been processed; the dilapidated and relentlessly leaking roof has been replaced with new iron sheets; the ceiling has been fixed; and the inner walls painted. More importantly, the library has opened its doors to the community. Challenges remain for this ongoing initiative, and include outdated and limited information resources, sustainability of library operations, space shortages and hygiene issues, including lack of restrooms. Strategies have been developed to deal with the mentioned challenges, though their implementation will depend on availability of resources. This paper describes the role librarians can play in uplifting the living conditions of people in rural areas by taking relevant information resources to these segregated, neglected and dejected communities.